The Impact of English Language Proficiency on Bank Employees’ Performance in Makassar - Marwah Juwita Yusuf; Indrayani Simpuruh; Syamsinar Syamsinar (Journal of English Language and Education, 2026)
This study aims to analyze the impact of English language proficiency on the performance of bank employees in Makassar. In the era of globalization and international banking services, English has become an essential communication tool for employees who interact with foreign customers, operate digital banking systems, and access global financial information. This research employed a quantitative research design using a survey method. The participants consisted of 25 bank employees from several banking institutions in Makassar selected through purposive sampling. Data were collected through a structured questionnaire using a five-point Likert Scale to measure employees’ English proficiency and job performance indicators, including work efficiency, communication skills, and career development opportunities. The collected data were analyzed using descriptive statistical analysis, including percentages, mean scores, and frequency distributions. The reliability test using Cronbach’s Alpha showed a reliability coefficient of 0.82, indicating that the instrument was reliable. The findings revealed that 60% of respondents had intermediate English proficiency, while 20% were categorized as advanced and 20% as beginner users. The overall mean score for employee performance was 4.12, indicating a high level of agreement that English proficiency positively influences workplace performance. Furthermore, 72% of respondents agreed that English proficiency improved communication with foreign clients, while 68% stated that it increased work efficiency and productivity. The study concludes that English language proficiency significantly contributes to employee performance, customer service quality, and career advancement opportunities in the banking sector. Therefore, banking institutions are encouraged to provide continuous English language training programs to strengthen employees’ competencies and organizational competitiveness.